Mário de Andrade e o estro romântico de sua propositura estético-musical: expressão da determinação histórica no capitalismo hiper-tardio - Carvalho, Henri de (2009)
The objective of this work is to insert the music esthetics of Mário de Andrade in a brazilian historical context, with a intriguing social transformation, taken into account the political and cultural transformations in the first half of twenty centuty It can be admitted that Mário de Andrade is a man who goes through different experiences related to modernity. Therefore, to understand his work it will be necessary to comprehend the establishment of the relations among modernity, historical experience and modernism. It has been as a reference the music composed by himself, something that seems to be the best way, having as criterion of study the emanate reading from the elements of his work, they demonstrate his main influences and intentions, historically warrantable in a country that has in its economic and social development features of colonialism. The duality of feeling provided for the experience in the modernity is between the threshold of living a revolutionary and materialistic progressive age, being at the same time present in a world that is not entirely materially and spiritually modern, exactly for attending to the needs and maintenance of exclusive interests of capitalism, and not to solve human nor social problems, historically present. Mário de Andrade romantism is in the simbolism psychological force, in militant art for a national cause, in the research of terrantesa music and in the systematical use of ithis like raw material to bring about erudit music. These three points have appeared in Mário de Andrade syntomatic expressions of a social organization that showed spirtually and materially, to take and carry with itself the real impressions of historical specification of economic development very late of capitalism in Brasil